11TH GRADE EFL LEARNERS’ PERCEPTION OF THE AUTHENTICITY OF THE NEW TEXTBOOK ENGLISH 11-TIENG ANH 11 (TẠP CHÍ KHOA HỌC TRƯỜNG ĐẠI HỌC TRÀ VINH, 2022)
This study investigated EFL students’ perceptions of the authenticity of texts and tasks within the new textbook Tieng Anh 11.The research followed a descriptive approach. The study collected data from questionnaires for 58 EFL students and interviews with six representative students at an upper secondary school in Mekong Delta area, Vietnam. Results from the questionnaire indicated that readings within the textbook were rated very positively while learning tasks received a less positive rating. Further interviews revealed that students emphasized the need for practical tasks for their reallife language use and the development of critical thinking.